Nutrition Diagnosis for Nitrogen in Winter Wheat Based on Critical Nitrogen Dilution Curves. Issue 1 (1st January 2018) - Yin, Minhua; Li, Yuannong; Xu, Luquan; Shen, Shenglong; Fang, Heng
ABSTRACT: Accurate and timely diagnosing of nitrogen (N) requirements for crop growth is vital for improving the efficiency of N use and reducing the risk of N losses. This study conducted a comparison of N dilution curves with urea and controlled‐release N fertilizer (CRN) to explore the applicability of critical N curve and to determine the appropriateness of CRN. Experiments on winter wheat ( Triticum aestivum L.) with different N applications were conducted during 2013 to 2015 in Shaanxi Province, China. The N applications consisted of urea at 80 (U80), 160 (U160), and 240 kg N ha −1 (U240), with 40% applied as a basal fertilizer and 60% topdressed at the jointing stage, and CRN at 60 (C60), 120 (C120), 180 (C180), and 240 kg N ha −1 (C240), all applied as a basal fertilizer. A treatment with no N application served as a control (CK). The critical N concentration and shoot dry matter of winter wheat fitted a power function for both CRN and urea. The curves were validated with data from another season, and their performances were proved to be stable. The estimated N nutrition index and accumulated N deficit under each N application enabled crop N condition to be well differentiated and suggested that a suitable N application rate for winter wheat was 120 to 180 kg CRN ha −1 and 160 to 240 kg urea ha −1 . Moreover, the C180 treatment produced a similar yield as the U240 treatment, but its N physiological efficiency, N agronomic efficiency, partial N productivity, and apparent N recovery were on average 5.87, 35.93, 34.12, and 28.39% higher than the U240 treatment, respectively, in the two seasons. These results are useful for N application management and can offer a theoretical reference for CRN application.